2011
DOI: 10.4028/www.scientific.net/msf.679-680.314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inter-Well Coupling between 3C and 6H in-Grown Stacking Faults in 4H-SiC Epitaxial Layers

Abstract: Abstract. Both 3C and 6H stacking faults have been observed in a low doped 4H-SiC epitaxial layer grown in a hot-wall CVD reactor on a heavily doped (off-axis) 4H-SiC substrate. They appear differently on the different parts of sample, with energetic dispersion ranging from 3.01 eV to 2.52 eV. Since they behave as natural type-II quantum wells in the 4H-SiC matrix, the thickness dependence of the excitonic recombination is investigated using the standard effective mass approximation. The results are discussed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A different group investigated stacking faults of lightly-doped 4H-SiC homo-epitaxial layers with HR-TEM observation and PL measurements at liquid helium temperature. 23,24) From HR-TEM observation, they reported that the stacking fault structure appears as an odd or even number of half-unit cells of 6H-SiC. They suggested that these types of stacking faults may contain both Frank-and Shockey-type stacking faults, and discussed the optical signature from a quantum well model.…”
Section: Off-direction [1120]mentioning
confidence: 99%
“…A different group investigated stacking faults of lightly-doped 4H-SiC homo-epitaxial layers with HR-TEM observation and PL measurements at liquid helium temperature. 23,24) From HR-TEM observation, they reported that the stacking fault structure appears as an odd or even number of half-unit cells of 6H-SiC. They suggested that these types of stacking faults may contain both Frank-and Shockey-type stacking faults, and discussed the optical signature from a quantum well model.…”
Section: Off-direction [1120]mentioning
confidence: 99%